2018
DOI: 10.1130/l690.1
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Upper Cretaceous Neo-Tethyan trench deposits in south Tibet (Luogangcuo Formation)

Abstract: Sedimentary basins within the Transhimalayan arc-trench system provide paleotectonic and paleogeographic information on the evolution of the late Mesozoic-early Cenozoic Neo-Tethyan subduction zone along the southern Asian margin. This paper presents detailed stratigraphic, sedimentologic, petrographic, detrital-zircon geochronologic and Hf isotopic data from the Luogangcuo Formation exposed as part of the Xiukang Mélange in south Tibet. The Luogangcuo Formation was deposited (ca. 88-81 Ma) in a trench environ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(34 citation statements)
references
References 91 publications
(171 reference statements)
3
31
0
Order By: Relevance
“…2). However, samples from turbidites in the Luogangcuo Formation appear qualitatively similar to our samples (An et al, 2018), suggesting that the coarse facies are likely a marginal or isolated trench slope basin equivalent of the Rongmawa Formation derived from local sources. Based on these provenance similarities and Late Cretaceous MDAs for all trench basin samples, we interpret that they comprised an interrelated trench basin (Fig.…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…2). However, samples from turbidites in the Luogangcuo Formation appear qualitatively similar to our samples (An et al, 2018), suggesting that the coarse facies are likely a marginal or isolated trench slope basin equivalent of the Rongmawa Formation derived from local sources. Based on these provenance similarities and Late Cretaceous MDAs for all trench basin samples, we interpret that they comprised an interrelated trench basin (Fig.…”
Section: Discussionsupporting
confidence: 70%
“…A different trench basin unit (Luogangcuo Formation) exposed near Saga (Fig. 1) was also deposited during Late Cretaceous time (88-81 Ma; An et al, 2018). It is distinguished based on its conglomeratic composition and DZ age spectra that largely lack the >170 Ma age-probability peaks (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This phenomenon is quite common in suture zones, such as the trench deposits of the Luogangcuo Formation (An et al, 2018) and the deep-sea turbidites in the Sangdanlin Section (Ding et al, 2005;DeCelles et al 2014;Hu et al, 2015Hu et al, , 2017 This Middle Jurassic Lhasa-Qiangtang initial collision time is coincident with that from a study in the southern Qiangtang basin in the Shuanghu area (Ma et al, 2017). Given these studies, it can be concluded that the Lhasa-Qiangtang initial collision occurred in Middle Jurassic time (~166 Ma) from Nima to Gaize along the BNSZ.…”
Section: Accepted Manuscriptsupporting
confidence: 52%
“…Thick‐bedded marbles indicate that protoliths of the Langxian unit could have been deposited in a shallow sea environment rather than in trench or trench‐slope basin. This is because trench or trench‐slope basin in the central YZSZ often comprises deep‐water deposits such as chert and turbiditic sandstone (An et al, 2018; Cai et al, 2012; Metcalf & Kapp, 2019; Wang et al, 2018) and receives detritus only sourced from magmatic arc, recycled accretionary wedge, or forearc sequences in the north (An et al, 2018; Cai et al, 2012).…”
Section: Discussionmentioning
confidence: 99%